Seeing how we see each other: learning from quantitative research among young people in the UK - Tania ap Siôn (Journal of beliefs and values, 2017)
The quantitative strand of the Young People's Attitudes towards Religious Diversity Project, conducted by the Warwick Religions and Education Research Unit, set out to capture data from over 2000 students living in each of the four nations of the United Kingdom (England, Northern Ireland, Scotland and Wales) and from London as a special case. Anonymity and confidentiality were assured. In total, nearly 12,000 students submitted thoroughly completed questionnaires. The project concentrated on schools within the state-maintained sector, but sought to obtain roughly equal numbers of students within each of the five areas attending schools with a religious character and without a religious foundation. The aim of the present paper is to collate, present and assess the findings from this survey that are relevant to the theme of this Special Issue, concerned with examining how a religion shapes the way of seeing the world and seeing other religious traditions. Highlights from the research include: students who are themselves religiously motivated hold more positive attitudes towards religious diversity; there is no evidence that schools with a religious character produce students who are less-accepting of people from other religious faiths; religious education does work in the sense of leading to attitudes that promote community cohesion, lessen religious conflict and promote the common good.